2012
DOI: 10.22358/jafs/66062/2012
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition and ruminal degradation of the protein and fibre of tetraploid <i>Robinia pseudoacacia</i> harvested at different growth stages

Abstract: Samples of leaves, stems and whole plant of tetraploid Robinia pseudoacacia harvested at four different growth stages (first rapid growth, slow growth, second rapid growth, and leaf-colour changing) were analysed for chemical composition and in situ disappearance of protein and fibre using the nylon bag technique. The crude protein content was the highest in leaves, followed by whole plant, and the lowest in stems, while the opposite trend was found for dry matter, NDF, and ADF. Moreover, the crude protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The decomposition rate of black locust (Robinia pseudoacacia L.) leaves was higher than that of oak leaves, most likely because of the higher N content in black locust leaves (Tateno et al, 2007). In the extract of Robinia pseudoacacia L. leaves the highest content of polyphenols and crude protein was found (Zhang et al, 2012;Marinas et al, 2014). Hassall & Dangerfield (1990) concluded that A. vulgare populations (Breckland district of East Anglia) are more likely to be regulated from "below" by competing for limited food (intra-specific competition) than from "above" by natural enemies.…”
Section: Discussionmentioning
confidence: 99%
“…The decomposition rate of black locust (Robinia pseudoacacia L.) leaves was higher than that of oak leaves, most likely because of the higher N content in black locust leaves (Tateno et al, 2007). In the extract of Robinia pseudoacacia L. leaves the highest content of polyphenols and crude protein was found (Zhang et al, 2012;Marinas et al, 2014). Hassall & Dangerfield (1990) concluded that A. vulgare populations (Breckland district of East Anglia) are more likely to be regulated from "below" by competing for limited food (intra-specific competition) than from "above" by natural enemies.…”
Section: Discussionmentioning
confidence: 99%
“…The tannin content in leaves ranged from 10 to 20 g · kg -1 in tetraploid R. pseudoacacia ) as compared with 65.9 to 104 g · kg -1 in diploid R. pseudoacacia (Negi et al, 1989;Unruh Snyder et al, 2007). Moreover, the content of crude protein (CP) and 18 amino acids (AA) in tetraploid R. pseudoacacia leaves can reach 270 g · kg -1 and 180 g · kg -1 , respectively, making the tree an excellent fodder for animals (Zhang et al, 2007(Zhang et al, , 2012. Moreover, no significant differences have been observed among goats fed R. pseudoacacia at 300-600 g · kg -1 in terms of average daily gain.…”
Section: Introductionmentioning
confidence: 99%